Gdańsk - Wrzeszcz, ulica Lendziona 8 - Nowaliński, Karol (1935- ). (Gdańsk, 1991)
Przedstawia kamienicę przy ul. Lendziona nr 8, 1991 r.
Tytuł i data ołówkiem na rewersie.
Keywords: Fotografie -- Polska -- Gdańsk; Ulice -- Polska -- Gdańsk -- 1945- -- fotografie; Gdańsk (Polska) -- 1970-2000 -- fotografie; Wrzeszcz (Gdańsk, Polska ; dzielnica) -- 1945- -- fotografie